Agricultural and mechanical colleges - Cavenaugh, William Annesley (My University, 1896)
Introduction: Since the foundation of the colonies on this continent, one of the first policies was to furnish to all of its people a means of securing a good common school education. As early as 16H9, before the foundation of the United States, we find that the New England States, Massachusetts in particular, made provisions for educating its people. Every township was required to maintain a school for teaching reading and writing, and to qualify the youth for higher and more thorough training. The people of our country have had exceptional educational opportunities of which they have duly taken advantage, and as a result they have today a school system that cannot be excelled by any other nation. The American educators have enlarged the utility of education and extended its range until now it has the most thorough system of education ever enjoyed by a country, and it cannot be more efficiently applied to the necessary avocations of live than it is today. Is it any wonder that we are proud of such a nation?
Citation: Cavenaugh, William Annesley. Agricultural and mechanical colleges. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Colonies; Education; Township; New England states; Theses; Manuscripts (documents)